Preservice Teachers’ Mathematical Mindsets During Pandemic-Induced Pivot to Online Learning - Cutler, Carrie S. (Frontiers in Education, 2020)
Many preservice teachers (PSTs) enter mathematics methods courses with fixed beliefs about teaching and learning mathematics and their own abilities as doers of mathematics. Using a repeated measures design, I examined changes in PSTs’ beliefs about mathematics teaching and learning at three separate time points–at the beginning of the first semester of a growth mindset-oriented mathematics methods course, midway through the treatment at the end of the first semester, and at the conclusion of the treatment at the end of the second semester of mathematics methods that was forced to pivot to online learning due to the COVID-19 pandemic. Results showed that explicit teaching of growth mindset principles coupled with participation in growth mindset-oriented mathematics methods courses yielded statistically significant improvement for PSTs’ beliefs about Rules and Procedures, Process of Inquiry, Active Learning, and Fixed Ability as measured by the TEDS-M instrument and did not appear to be impacted by the pivot to remote learning. Comparison of a pre-pandemic cohort with the pandemic-disrupted cohort showed no statistically significant difference in Fixed Ability. These findings suggest that resilience, one of the hallmarks of the growth mindset, may serve as a protective asset during periods of profound stress.